2005
DOI: 10.1016/j.cell.2005.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Pol II Transcripts Are Degraded by a Nuclear Quality Control Pathway Involving a New Poly(A) Polymerase

Abstract: Since detection of an RNA molecule is the major criterion to define transcriptional activity, the fraction of the genome that is expressed is generally considered to parallel the complexity of the transcriptome. We show here that several supposedly silent intergenic regions in the genome of S. cerevisiae are actually transcribed by RNA polymerase II, suggesting that the expressed fraction of the genome is higher than anticipated. Surprisingly, however, RNAs originating from these regions are rapidly degraded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
985
4
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 772 publications
(1,041 citation statements)
references
References 40 publications
45
985
4
7
Order By: Relevance
“…Both the Nrd1/Nab3/Sen1 complex, which binds CUTs in a sequence dependent manner, 14 and modification of CUTs by addition of a short polyA tract by the Trf-Air-Mtr4 polyadenylation (TRAMP) complex activate exosome-mediated degradation. 15,16 This exosome-dependent degradation explains why the CUTs are rarely seen in genomic assays.…”
Section: Divergent Transcription In Mammalsmentioning
confidence: 99%
“…Both the Nrd1/Nab3/Sen1 complex, which binds CUTs in a sequence dependent manner, 14 and modification of CUTs by addition of a short polyA tract by the Trf-Air-Mtr4 polyadenylation (TRAMP) complex activate exosome-mediated degradation. 15,16 This exosome-dependent degradation explains why the CUTs are rarely seen in genomic assays.…”
Section: Divergent Transcription In Mammalsmentioning
confidence: 99%
“…The Nrd1 complex has wider functions in gene expression, especially in the synthesis/processing of CUTs. CUTs are short noncoding RNAs (300-600 nt) that were first detected by genome-wide microarray analysis in yeast strains defective for RNA nuclear degradation (Kapranov et al 2005;Wyers et al 2005;David et al 2006;Davis and Ares 2006). In strains defective for the nuclear exosome protein Rrp6, CUTs with a defined 59-end and heterogenous 39-ends accumulate.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…These transcripts are estimated to originate from 10% of yeast intergenic regions (Wyers et al 2005; although see Neil et al 2009 andXu et al 2009). After Nrd1-dependent termination by RNAPII, CUTs are rapidly polyadenylated by the TRAMP complex, and then degraded by the nuclear exosome (Wyers et al 2005;Arigo et al 2006b;Houalla et al 2006;Thiebaut et al 2006). Recently, Gudipati et al (2008) showed that Nrd1-dependent termination of CUTs is inhibited by CTD phosphorylation on Ser2 and promoted by Ser5 phosphorylation.…”
Section: A Wider Role For the Nrd1 Complex In Gene Expressionmentioning
confidence: 99%
“…It is involved in the surveillance of mRNA biogenesis, the cytoplasmic turnover of mRNA, and the degradation of unstable transcripts derived from intergenic regions in the genome of the S. cerevisiae (Wyers et al, 2005;Preker et al, 2008). The exosome also plays an essential role in the processing of noncoding RNA precursors, including pre-rRNA, pre-snRNA, pre-snoRNA, and pre-tRNA (reviewed by Butler, 2002).…”
Section: Introductionmentioning
confidence: 99%